P.2.04 Occupational skin disease in a tertiary occupational dermatologic clinic: a retrospective analysis from 2010 to 2017. (April 2019) - Chang, Heng-Hao; Wang, Bour-Jr; Guo, How-Ran; Lee, I-Ru
Abstract : Background: Occupational skin disease (OSD) is one of the most common occupational disorders in Taiwan. As reporting OSD was not compulsory, there was limited information on the exact causes and patient characteristics. The objective of this study was to investigate the causes and common allergens among OSD patients in Taiwan. Methods: We recruited patients from Occupational Dermatology Clinic in National Cheng Kung University Hospital, a tertiary referral center in Tainan city, between 1 January 2010 and 31 July 2017. Patch testing with European baseline series, additional occupation-oriented series, and personal material exposed at work or during daily life was carried out if the patients were suspected of allergic skin diseases. Results: Among the 273 patients who received patch testing, 51 (18.7%) patients had a final diagnosis of OSD. 82.4% of the 51 patients were diagnosed with allergic contact dermatitis (ACD), 11.8% with irritant contact dermatitis (ICD), while the rest 5.9% with both. Patient reported 3.0 years of skin problem prior to the clinic visit. The vast majority of patients suffered from hand eczema. Epoxy resin workers, food workers, hairdressers and beauty salon beauticians were the most common occupations related to OSD. The most important allergens were nickel, fragrance mix I, potassium dichromate and paraben mix. Around half of the patients showed allergic reaction to their personal material. Discussion: As worker compensation statistics may not accurately estimate the characteristics of OSD patients, our study was crucial to identify the high-risk groups as well as the common allergens related to their work. Although the results might not represent the proportion of patients of OSD in other clinic, drawing information from patch testing may reflect those patients of severer or longer duration of symptoms. Future occupational measures should be taken on these industries for the detection and prevention of OSD.